Veil of shadows - Hunter, Erin (Hunter, Erin. Warriors, the broken code ;, 2021)
"With an impostor leading ThunderClan, threatening to exile any cats who challenge him, a small but growing group of cats must find a way to expose the truth and return ThunderClan's rightful leader-before the tensions among the Clans erupt into war"--Provided by publisher.